2022
DOI: 10.3390/life12020265
|View full text |Cite
|
Sign up to set email alerts
|

Differential Oligomerization of Alpha versus Beta Amino Acids and Hydroxy Acids in Abiotic Proto-Peptide Synthesis Reactions

Abstract: The origin of biopolymers is a central question in origins of life research. In extant life, proteins are coded linear polymers made of a fixed set of twenty alpha-L-amino acids. It is likely that the prebiotic forerunners of proteins, or protopeptides, were more heterogenous polymers with a greater diversity of building blocks and linkage stereochemistry. To investigate a possible chemical selection for alpha versus beta amino acids in abiotic polymerization reactions, we subjected mixtures of alpha and beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Polyester synthesis could have been driven by wetdry cycles on early Earth in evaporative environments [14] or through precipitation and temperature cycling. [15] Mixed depsipeptide products, produced from dehydration synthesis of 𝛼HA and amino acid monomer solutions, have been shown to be produced under similar wet-dry conditions, [16,17] and some depsipeptides can perform prebiotically relevant functions such as RNA stabilization. [18] Dehydration polymerization of a wide variety of 𝛼HAs has also been shown to produce both linear [12,19] and branched [20,21] polyesters.…”
Section: Introductionmentioning
confidence: 99%
“…Polyester synthesis could have been driven by wetdry cycles on early Earth in evaporative environments [14] or through precipitation and temperature cycling. [15] Mixed depsipeptide products, produced from dehydration synthesis of 𝛼HA and amino acid monomer solutions, have been shown to be produced under similar wet-dry conditions, [16,17] and some depsipeptides can perform prebiotically relevant functions such as RNA stabilization. [18] Dehydration polymerization of a wide variety of 𝛼HAs has also been shown to produce both linear [12,19] and branched [20,21] polyesters.…”
Section: Introductionmentioning
confidence: 99%
“…MALDI was also hindered by the presence of minerals and salts in simulated space dust. In previous prebiotic studies on depsipeptides, amino acid conversion was typically determined by NMR. ,, Like MS, NMR analysis can be difficult in complex sample matrices. With further investigation, it is hypothesized that differential FTIR may be capable of relative quantitation of ester/amide ratios via analysis of standards with known ester and amide content, even in complex matrices.…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory research has shown that RNAs alone [24] or peptides alone [25] can form self-reproducing networks. Peptides can also self-condense and recombine through wet–dry cycles, aided by thioester chemistry [26,27]. Simple amino acids such as glycine and alanine can moreover be driven by carbonyl sulfide gas into ordered amyloid fibres that in turn drive the formation of more complex structures [28].…”
Section: Resultsmentioning
confidence: 99%